2021
DOI: 10.1111/deci.12510
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lean implementation on hospital financial performance

Abstract: This study examines lean implementation's effects on hospital financial performance using survey and secondary data for a large sample of US hospitals. Using sociotechnical systems theory, a social context is identified that should motivate the use of lean process improvement tools (LPT) in a hospital setting and accentuate its performance benefits. Shah and Ward's employee involvement (EI) construct is adapted to a hospital setting to define a supportive social context for LPT, which is further shaped by orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 123 publications
0
37
0
Order By: Relevance
“…Psychological safety is a concept largely used in the literature to explain the efficacy of teams in terms of learning, creativity and engagement, but scarcely applied to the lean literature. Our study builds upon the few previous exploratory studies in which psychological safety emerges as a key aspect of a lean culture (Mazur et al, 2012;Narayanan et al, 2021;Love et al, 2021;Rojas et al, 2021) and those that state that (lean) leaders have an effect on their subordinates' psychological safety (Van Dun and Wilderom, 2016a;Latif et al, 2021). We thus further the understanding of this team emergent state for the materialisation of lean into learning.…”
Section: Implications For Researchmentioning
confidence: 74%
See 2 more Smart Citations
“…Psychological safety is a concept largely used in the literature to explain the efficacy of teams in terms of learning, creativity and engagement, but scarcely applied to the lean literature. Our study builds upon the few previous exploratory studies in which psychological safety emerges as a key aspect of a lean culture (Mazur et al, 2012;Narayanan et al, 2021;Love et al, 2021;Rojas et al, 2021) and those that state that (lean) leaders have an effect on their subordinates' psychological safety (Van Dun and Wilderom, 2016a;Latif et al, 2021). We thus further the understanding of this team emergent state for the materialisation of lean into learning.…”
Section: Implications For Researchmentioning
confidence: 74%
“…Earlier studies have investigated psychological safety as an antecedent to lean implementation (e.g. Narayanan et al, 2021) or as a mediator to lean's effect on performance (e.g. Love et al, 2021), but we see psychological safety as a possible outcome of lean implementation (see also Rojas et al, 2021).…”
Section: Leanness and Team Psychological Safetymentioning
confidence: 84%
See 1 more Smart Citation
“…For those hospitals who have published on lean and nancial results, another interesting question may be whether they causative or just correlative? Narayanan, Vickery (17) note that lean implementation studies have generally found a positive correlation with revenue increases as the primary positive nancial impact of PI. These studies have all been in the US, where increased e ciency and throughput is likely to be associated with 'doing more work' which in turn generates more income.…”
Section: Principal Ndingsmentioning
confidence: 99%
“…, much of the available research is concerned with "…. process performance and clinical performance…" of PI initiatives (17). This is not unique to hospitals with a literature review conducted in nonhealthcare industries nding that information on how companies determine the economic value or nancial bene ts derived from PI initiatives is scarce (13).…”
Section: Theorymentioning
confidence: 99%